READING SĪTĀ’S LETTER ON OLD JAVANESE RĀMĀYAṆA KAKAWIN ON THE BASIS OF CANDRAKIRAṆA AS PROSODIC TREATISE - Zakariya Pamuji Aminullah (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
The study presented in this article focuses on the signification of the poetic metres and the theory of rasa expounded in Candrakiraṇa, a guide to the composition of kakawin that is preserved in the scriptoriums of mountains. The use of the poetic metres and theory of rasa was examined in the text of Sītā’s letter to Rāma that was taken from the Rāmāyaṇa Kakawin. It was carried out on the three manuscripts of Candrakiraṇa preserved by the National Library of Indonesia (PNRI). The findings show that the use of śārdūlawikriḍita metre in Sītā’s letters results in a form of signification for particular aesthetic experiences (rasa), namely karuṇa (sympathy), bhayānaka (concern), śānta (peace) and śṛṅgara (love). Tulisan ini berfokus pada metrum dan teori rasa sebagai sarana pemaknaan yang dimuat dalam Candrakiraṇa, sebuah pedoman penulisan kakawin yang diwariskan di skriptorium-skriptorium pegunungan. Metrum dan teori rasa tersebut dikaji penggunaannya dalam surat Sītā kepada Rāma yang terkandung dalam Kakawin Rāmāyaṇa. Kajian ini melibatkan tiga manuskrip yang merupakan koleksi Perpustakaan Nasional Republik Indonesia. Hasil analisis menunjukkan bahwa metrum śārdūlawikriḍita yang digunakan pada surat Sīta menunjukkan bentuk pemaknaan untuk pengalaman-pengalaman estetika (rasa) tertentu, yaitu karuṇa (belas kasihan), bhayānaka (kekhawatiran), śānta (damai) dan śṛṅgara (cinta).